Le mahdi Ibn Tûmart et al-Andalus : l'élaboration de la légitimité almohade - Maribel Fierro (Revue des Mondes Musulmans et de la Méditerranée)
Mahdism is one of the means offered by Islamic tradition to legitimize a ruler. It is of special relevance when the aim is to renovate society and to eliminate old politico-religious elites and create new ones. Mahdism might be seen as the continuation of the model khalifat Allâh, i. e., the ruler as delegate or representative of God on earth, a model that was preserved by the Shiites but which the Sunnites eventually discarded in favour of the model khalifat rasûl Allâh. Yet, the model has resurfaced in the Sunni community in differents periods and in different forms. The Almohad period (12th century) was one of them. This paper shows how Almohad Mahdism was shaped as a response to the political and religious establishment that the Almohads encountered when they conquered al-Andalus.